Les Monomanes de Géricault : une vie infâme dans l’histoire de l’art - Morad Montazami (Images Re-Vues, 2014)
At the crossroads of art history and psychiatry, theories of the portrait and theories of the symptom, history of the gaze and that of scientific objectification, Géricault's Monomanes do turn into a "legend". Such a legend escapes us and periodically reappears at the limit between the various discourses that these "portraits of the insane" generate, illustrate and justify. I may try to put in perspective their modes of existence in terms of the Archaeology of knowledge inherited from Michel Foucault.